Meritve in validacija sklopljenosti in gostote magnetnega polja pri brezžičnem prenosu energije z razsmernikom D-razreda - Domajnko, Jure (visokošolska dela, 2022)
The thesis presents the development of the measurement equipment, that can be used during the design of the wireless power transfer systems. The wireless power transfer systems are more complex compared to the wired, plug-in charging. This complexity makes the development of the wireless power transfer systems more difficult. The most important parameters of the inductive wireless power transfer systems are the coupling coefficient between the transmitter and the receiver coil, and the magnetic flux density that transfers the power from primary to secondary side. The coupling coefficient impactson the system efficiency. Due to the large air gap between the transmitter and the receiver coil, the coupling coefficient is low. In the case of the misalignment between the coils, the coupling coefficient additionally decreases. To help with the iterative wireless power transfer coil design process, the measurement system was developed. The measurement system measuresthe coupling coefficient between the transmitter and the receiver coil in 3D space.The magnetic flux density impacts on the coupling coefficient and on radiate magnetic fieldduring the coil integration process. The developed magnetic field measurement system enablesmeasurement of the magnetic filed, generated by the transmitter coil, excited by theclass D inverter.
Keywords: Brezžični prenos; class D inverter; coupling coefficient; Disertacije; doktorske disertacije; Energija; gostota magnetnegapolja; inductive power transfer; induktivni prenos energije; koeficient sklopljenosti; magnetic flux density; magnetometer; magnetometri; Merilni sistemi; razsmernik razreda D